Modelling the Image Research of a Tourism Destination - Nicolae Teodorescu; Ion Pârgaru; Aurelia-Felicia Stancioiu; Elena Matei (Amfiteatru Economic Journal, 2014)
The problematic area of the tourism destination image has a high expansion in marketing, the efforts of its conceptualization and phenomenalism being remarkable among specialists. In this context, the authors propose a systemic approach, the result of which refers to a model regarding the image research of a tourism destination, whose validation has been attained using Transalpina destination. The model created by the authors envisages morphological features and specific functional relationships, which are consistent with the marketing theory, and, in context, with the consumer behaviour theory. The conceptualmethodological solutions are magnified by applicative-experimental validations, which enhance the theoretical and practical valences of the created model. The main direction of developing the elaborated model consists in efforts of formalization and abstracting, in the perspective offered by several scientific disciplines.
Keywords: M31; 330; destination image; image modelling; Transalpina destination